The role of rural-based municipalities to promote socio-economic development : the case of Molemole and Blouberg Municipalities in Limpopo Province - Modisha, Nkoto Johannes (University of Limpopo (Turfloop Campus), 2013)
his article measures the expectations of citizens against local government‟s legislative mandate to deliver services to citizens within the context of the Molemole and Blouberg Municipalities in Limpopo. In doing so, it aims to contribute the discourse on governance from the perspective of the governed. The qualitative study utilized purposive sampling and collected data using unstructured questionnaires; individual and focus group interviews, observation and participatory tools. The key findings are that citizens in the study area are in dire need of the following services: water, electricity, sanitation and sewerage, road maintenance services, housing, refuse removal and health services in that order; and that citizens were unclear about the functions of national, provincial and local government in relation to housing, health and other services. They felt that a local municipality has the responsibility to tar and maintain roads within its jurisdiction, including district roads and even to provide housing and health services. They also felt that, while local government is touted as the sphere that brings government closer to the people, it has not been accorded the necessary powers and functions to provide basic services to communities at a satisfactory level. As a result, since the dawn of democracy in South Africa, communities have lost faith in the ability of local municipalities to improve their welfare. Key words: service delivery, governance, municipalities, essential services
Thesis (MPA) --University of Limpopo, 2012
Keywords: Local governments; Municipalities; Service delivery; Governance; Essential services; 320.84; Service delivery; Local Government -- South Africa -- Limpopo